NANOSTRUCTURES IN THE SURFACE LAYERS OF COAL MATTER - Portnov, V.; Yurov, V.; Reva, N.; Mausymbaeva, A.; Imanbaeva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
According to modern concepts, the surface layer of compounds is understood as the ultrathin cover, the properties, structure and composition are different from the crystalline substrate with this layer and this layer is in thermodynamic equilibrium. The surface layer consists of two layers - d(I) with thickness h = d, at which the phase transition occurs, and d(II) with the lower limit h≈10d, at which the physical properties of the crystal begin to manifest themselves. The thickness of the surface layer d(I) is determined by one fundamental parameter, the molar (atomic) volume of the element (= M/ρ, M is molar mass (g/mol), ρ is density (g/cm3)). The average statistical structural unit of coal corresponds to higher fullerenes with the number of carbon atoms in the cluster >100, which is the unique feature of the coal substance, which is not a crystalline structure, but a complex polymer with a supramolecular structure. The thickness of the surface layer of the coal substance is two orders of magnitude greater than the thickness of pure metals and is close to the thickness of the surface layer of higher fullerenes C96 (135 nm). The increasing of the coal substance’s porosity of 90 % is led to increasing the thickness d(I) of the surface layer by the order of magnitude, that is 2 microns. In this regard, the "apparent" change in the radius of a coal particle means a change in its mass, proportional to the release of methane from the solid solution. The dependence of the complete decomposition’s time of coal methane is 0 on the parameter |λ|. The equation which is obtained, includes the ratio of the heat flux introduced into the reservoir volume due to the internal heat release process to the heat flux which is carried away from the volume due to thermal conductivity. If this ratio exceeds a certain critical value of the unity’s order, the thermal explosion occurs, leading to the decomposition of coal methane. The size effects in the d(I) layer are determined by the entire group of atoms in the system (collective processes). Such "quasi-classical" size effects are observed only in nanoparticles and nanostructures. The d(I) layer for coal matter extends from 151.5 nm (Anthracite) to 214.2 nm (Brown). The dimensional temperature of the carbon nanoparticle at the initial temperature T0 = 300 K will be at least Tm = 872 K. This corresponds to particles of the order of half a micron. Coal particles with the radius of about one micron (or marked half a micron) in the case of decomposition of coal matter are heated to temperatures at which spontaneous combustion of nanoparticles is possible. Hygroscopic moisture in the genetic line of coal has the certain pattern of change and correlates with the thickness of their surface layer.